Spinodal decomposition and the pseudo-binary decomposition in high-entropy alloys - Luan, Hengwei; Huang, Liufei; Kang, Jingyi; Luo, Bosang; Yang, Xinglong; Li, Jinfeng; Han, Zhidong; Si, Jiajia; Shao, Yang; Lu, Jian; Yao, Ke-Fu (Acta materialia, 2023)
High-entropy alloys (HEAs) have many attractive properties, while the thermodynamic mechanism and general behavior of the spinodal decomposition in HEAs remain unknown. In this work, we conduct an experimentally consistent calculation of the spinodal decomposition of HEAs. Against the “high mixing entropy” theory, we show that increasing the number of elements can increase the possibility of spinodal decomposition, and the effects of the temperature, entropy and enthalpy are clarified. The high entropy effect on the widely observed pseudo-binary decomposition is proposed. These results provide a necessary paradigm to understand and further harness the spinodal decomposition in HEAs. [Display omitted]